LE SENS CONNOTATIF A TRAVERS L’EPITHALAME NANDE : CAS DE LA COMMUNE DE KAYNA AU SUD DU TERRITOIRE DE LUBERO - Flammarion, Dongola Kikuni; Jonathan, Kasereka Lukulirwa (IJRDO - Journal of Social Science and Humanities Research, 2023)
The present study went from a fundemental question that consisted  of some mechanism which should depictan allow people to discover the implicit and explicit meanings tha are hidden in epithalamium oral of oral literature.                     Taking into account the same question, this work tried to provide the reader with a given number of strategies and methods, especially literary ones that can help people to know the hidden meanings that are conveyed in nuptial songs that are from Nande.                     It also helps or aims at describing the style which is used by Nande community to teach and and give pieces of advice to people who are concerned with the wedding ceremony. This study aims also at helping people to render authentic their weddings by respecting all the legal steps required everywhere in the society, in the church and family.                     From different approaches, like stylistic, thematic and semiotic and some technics, we have discovered that epithalamiums are educational and relavant in the society;                     We reached this level after investigation and interview that proved us that through out four musical songs and stanzas of irregular measures, the literal and literary interpretation gave us some samples composed of great stylistic figures of speach like metaphor, metonyny, synecdoche, etc.                     We also discovered some themes that deal with moral, hospitality,patience, basic education, social integration, responsibility, relationship of spouses and the share of enheritance. Apart from all given above, we also discovered the social - cultural value that is embodied in the clan, the society, the community and the ancestral traditions.